Direct α-Trifluoromethylthiolation of Carboxylic Acids Enabled by Boron Catalysis - Sun, Kai; Huang, Chung-Yang Dennis; Sawamura, Masaya; Shimizu, Yohei (Synlett, 2023)
A boron-catalyzed direct α-trifluoromethylthiolation of carboxylic acids was developed. Catalytically generated boron enediolates reacts with electrophilic SCF3 reagent, N-SCF3-phthalimide, to provide α-SCF3 carboxylic acids without the need of substrate pre-activation. The method is applicable to direct modification of bioactive carboxylic acids. Data science analyses provided suitable models for substrate classification as well as yield prediction.
Keywords: carboxylic acid; boron catalyst; trifluoromethylthiolation; data science; drug modification; fluorine compounds